2009
DOI: 10.1002/14651858.cd001096.pub2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of on-screen, point of care computer reminders on processes and outcomes of care

Abstract: Background The opportunity to improve care by delivering decision support to clinicians at the point of care represents one of the main incentives for implementing sophisticated clinical information systems. Previous reviews of computer reminder and decision support systems have reported mixed effects, possibly because they did not distinguish point of care computer reminders from e-mail alerts, computer-generated paper reminders, and other modes of delivering ‘computer reminders’. Objectives To evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
343
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(368 citation statements)
references
References 478 publications
19
343
4
2
Order By: Relevance
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
“…In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior. 24 Our study adds to the small number of studies in this area, and appears to confirm the finding that CCDS instruments are equally effective at increasing and decreasing behaviors. It also demonstrated a significant change in provider behavior, despite a relatively small gap in quality.…”
Section: Discussionsupporting
confidence: 82%
“…Computer reminders to professionals at the point of care show 'small to modest improvements' in professional behaviour, but studies are heterogeneous and interventions complex, making these difficult to understand [49].…”
Section: Telemedicine Is Effectivementioning
confidence: 99%
“…En el caso de la auditoría y retroalimentación, los mayores efectos se observaron en aquellos casos con adherencia basal más baja 40 . Finalmente, en el caso de los recordatorios la mayoría de los estudios han evaluado intervenciones relativamente simples dirigidas a modificar comportamientos de baja complejidad (por ejemplo, prescripción) 41 .…”
Section: Difusión Diseminación E Implementación De Gpcunclassified